2020
DOI: 10.3390/rs12244020
|View full text |Cite
|
Sign up to set email alerts
|

A Deep Learning Method for Mapping Glacial Lakes from the Combined Use of Synthetic-Aperture Radar and Optical Satellite Images

Abstract: Glacial lakes (GLs), a vital link between the hydrosphere and the cryosphere, participate in the local hydrological process, and their interannual dynamic evolution is an objective reflection and an indicator of regional climate change. The complex terrain and climatic conditions in mountainous areas where GLs are located make it difficult to employ conventional remote sensing observation means to obtain stable, accurate, and comprehensive observation data. In view of this situation, this study presents an alg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…The evaluation results of these U-Nets are detailed in Table 1. In addition to the four fusion methods and ACFNet mentioned in Section 3, we also trained and evaluated Wu's model [46] and two other classical semantic segmentation models (SegNet and DeepLabV3+). Similar to ACFNet, Wu's model was proposed to extract glacial lakes based on optical and SAR images.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The evaluation results of these U-Nets are detailed in Table 1. In addition to the four fusion methods and ACFNet mentioned in Section 3, we also trained and evaluated Wu's model [46] and two other classical semantic segmentation models (SegNet and DeepLabV3+). Similar to ACFNet, Wu's model was proposed to extract glacial lakes based on optical and SAR images.…”
Section: Resultsmentioning
confidence: 99%
“…This study did not improve the network specially and just used SAR images. Wu et al proposed a model based on U-Net for glacial lake extraction using a combination of Landsat 8 optical images and Sentinel 1 SAR images [46]. Their research showed that the addition of SAR features helps to identify glacial lakes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The quality and quantity of training data are highly important [34,35] In general, the use of satellite images for the monitoring of glacial lakes has been mostly concerned with conventional manual digitization, edge detection, image segmentation methods, and object-oriented classification, rarely adopting some advanced deep-learning methods. Compared with other methods, deep-learning algorithms have a high ability in terms of feature extraction and autonomous learning; they possess a large number of hidden layers and can support a higher level of data abstraction and prediction.…”
Section: Fast and Parallel Computing Produces Full Boundariesmentioning
confidence: 99%
“…An attempt has been made recently to map glacial lakes using deep-learning models. Wu et al, 2020 presented an improved U-Net-based, deep-learning, semantic-segmentation network model for extracting the unconnected small glacial lake outlines using a combination of Sentinel-1 ground-range-detected (GRD) SAR images and Landsat-8 multispectral imagery data [34]. Qayyum et al, 2020 explored the potential of PlanetScope optical imagery for the mapping of glacial lakes in the different years over the Hindu Kush, Karakoram, and Himalayan region.…”
Section: Fast and Parallel Computing Produces Full Boundariesmentioning
confidence: 99%